Seismic retrofit and repair of existing reinforced concrete bridge columns by transverse prestressing - Yarandi, Majid Sadoughi (University of Ottawa (Canada), 2007)
Performance of bridges during recent earthquakes has revealed inadequacies of pre-1970's designs, especially in concrete columns. The 1989 Loma Prieta and 1994 Northridge earthquakes in California, and the 1995 Kobe earthquake in Japan, after the 1971 San Fernando earthquake, have demonstrated seismic deficiencies and resulting damage to a considerable number of major bridges. The deficiencies in bridge columns essentially stem from lack of properly designed transverse reinforcement, increasing their vulnerability to shear, confinement and reinforcement splice failures. The Structures Laboratory of the University of Ottawa has been active in developing new and effective seismic retrofit techniques. One such technique involves the transverse prestressing of concrete columns to improve concrete confinement, diagonal tension capacity and bond between steel and concrete in reinforcement splice regions. The technique, named as Retro-belt, has been verified through extensive experimental and analytical research on circular and square columns. However, questions remain in terms of its applicability to rectangular columns with a significantly different aspect ratio than square sections as well as its use as a repair technique. The objective of the current research effort is to extend the applicability of the Retro-belt technique to rectangular columns as well as explore the possibility of using it as a repair methodology. The research presented in this thesis consists of experimental and analytical phases. The experimental phase includes the tests of nine full-size bridge columns under simulated seismic loading. Three pairs of rectangular columns were designed, built and tested to extend the retrofit technique to rectangular columns. Three additional columns with circular, square and rectangular cross sections were designed and built as shear dominant columns to be damaged and repaired. They were damaged by initial loading, repaired by transverse prestressing and then retested to develop a repair methodology involving the Retro-belt technique. The analytical research was carried out to verify the applicability of existing design principles to columns that are transversely prestressed. Strength and deformability of columns computed by analytical means and recorded experimentally were compared to verify the analysis techniques. Design procedures were developed for retrofitting rectangular columns with shear, confinement and splice deficiencies. A repair design method was also proposed based on limited test data, to be further developed. The results indicate that pre-1970's columns suffer from lack of strength and deformability. Shear- and splice-deficient columns showed limited deformability of about 1% drift ratio. Columns that lacked confinement and behaved predominantly in the flexure mode developed approximately 2% lateral drift before they failed in a brittle manner. Those retrofitted by transverse prestressing showed improved deformability of approximately 4% lateral drift, indicating the effectiveness of the Retro-belt techniques as a seismic retrofit methodology for rectangular columns. The application of transverse prestressing as shear repair techniques was explored through testing. The test results showed that the Retro-belt technique was effective in restoring shear strength of a damaged column and improving its deformability from 1% to 4% lateral drift. However, the technique, as applied in the current investigation, demonstrated only a limited improvement when used for repairing a splice-deficient column. Further research is needed to develop the column repair technology.
Keywords: Engineering, Civil.